Challenges in the development of nanoparticle‐based imaging agents: Characterization and biology. (23rd August 2020) - Crist, Rachael M.; Dasa, Siva Sai Krishna; Liu, Christina H.; Clogston, Jeffrey D.; Dobrovolskaia, Marina A.; Stern, Stephan T.
Abstract: Despite imaging agents being some of the earliest nanomedicines in clinical use, the vast majority of current research and translational activities in the nanomedicine field involves therapeutics, while imaging agents are severely underrepresented. The reasons for this lack of representation are several fold, including difficulties in synthesis and scale‐up, biocompatibility issues, lack of suitable tissue/disease selective targeting ligands and receptors, and a high bar for regulatory approval. The recent focus on immunotherapies and personalized medicine, and development of nanoparticle constructs with better tissue distribution and selectivity, provide new opportunities for nanomedicine imaging agent development. This manuscript will provide an overview of trends in imaging nanomedicine characterization and biocompatibility, and new horizons for future development. This article is categorized under: Diagnostic Tools > in vivo Nanodiagnostics and Imaging Toxicology and Regulatory Issues in Nanomedicine > Toxicology of Nanomaterials Toxicology and Regulatory Issues in Nanomedicine > Regulatory and Policy Issues in Nanomedicine Abstract : The ideal imaging nanoparticle will avoid the mononuclear phagocytic system (liver), rapidly accumulate in target tissue by receptor‐mediated transcytosis or passive/active targeting mechanisms, and undergo renal elimination to increase signal/background.